Strategi Deiktis dan Dinamika Kesantunan dalam Bahasa Lauje: Analisis Sosiopragmatik Bahasa Austronesia yang Terancam Punah - Nizrawati, Nizrawati; Suputra, Gusti Ketut Alit; Ulinsa, Ulinsa (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
This study investigates deixis in the Lauje language from a sociopragmatic perspective, focusing on its forms, functions, and relationship with social factors in natural interaction. The research aims to identify the types of deixis used in Lauje and to explain how social variables influence their selection in everyday communication. The study employs a qualitative descriptive method using naturally occurring speech data collected from native Lauje speakers in Ogoansam Village, Palasa District, Parigi Moutong Regency, Central Sulawesi. Data were obtained through participant observation, semi-structured interviews, and audio recordings of spontaneous conversations. The analysis reveals that the Lauje language exhibits a comprehensive deixis system, encompassing person, place, time, discourse, and social deixis. Person and social deixis display significant variation in response to speakers’ age, social status, and degree of interpersonal closeness, reflecting norms of politeness and social hierarchy within the Lauje community. Place and time deixis function to anchor utterances within specific spatial and temporal contexts, while discourse deixis contributes to coherence and continuity in interaction. These findings demonstrate that deixis in Lauje functions not only as a referential linguistic device but also as a sociocultural strategy for managing social relations, maintaining interactional harmony, and expressing cultural identity. This study contributes to sociopragmatic research on minority languages and supports efforts in linguistic documentation and language preservation.